Comparison of the Amount of Temperature Rise in the Pulp Chamber of Teeth Treated with QTH, Second and Third Generation LED Light Curing Units: An In Vitro Study - Mahant, Rajesh Harivadanbhai; Chokshi, Shraddha; Vaidya, Rupal; Patel, Pruthvi; Vora, Asima; Mahant, Priyanka (Journal of Lasers in Medical Sciences, 2016)
Introduction: This in vitro study was designed to measure and compare the amount of temperature rise in the pulp chamber of the teeth exposed to different light curing units (LCU), which are being used for curing composite restorations. Methods: The study was performed in two settings; first, an in vitro and second was mimicking an in vivo situation. In the first setup of the study, three groups were formed according to the respective three light curing sources. i.e. Quartz-Tungsten-Halogen (QTH) unit and two light-emitting diode (LED) units (second and third generations). In the in vitro setting, direct thermal emission from three light sources at 3 mm and 6 mm distances, was measured with a k-type thermocouple, and connected to a digital thermometer. For a simulation of an in vivo situation, 30 premolar teeth were used. Class I Occlusal cavity of all the teeth [RM1] were prepared and they were restored with incremental curing of composite, after bonding agent application. While curing the bonding agent and composite in layers, the intrapulpal temperature rise was simultaneously measured with a k-type thermocouple. Results: The first setting of the study showed that the heat produced by irradiation with LCU was significantly less at 6 mm distance when compared to 3 mm distance. The second setting of the study showed that the rise of intrapulpal temperature was significantly less with third generation LED light cure units than with second generation LED and QTH light cure units. Conclusion: As the distance from the light source increases, less irradiation heat is produced. Third generation LED lights cause the least temperature change in the pulp chamber of single rooted teeth.